The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23052853
|View full text |Cite
|
Sign up to set email alerts
|

Blood Thiol Redox State in Chronic Kidney Disease

Abstract: Thiols (sulfhydryl groups) are effective antioxidants that can preserve the correct structure of proteins, and can protect cells and tissues from damage induced by oxidative stress. Abnormal levels of thiols have been measured in the blood of patients with moderate-to-severe chronic kidney disease (CKD) compared to healthy subjects, as well as in end-stage renal disease (ESRD) patients on haemodialysis or peritoneal dialysis. The levels of protein thiols (a measure of the endogenous antioxidant capacity invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 149 publications
0
3
0
Order By: Relevance
“…These latter include the transcriptional and metabolic processes associated with adaptive homeostasis mechanisms discussed earlier in Section 2 , and these defects are exacerbated in case of premature aging and oxidative stress induced by chronic and degenerative ailments. For example, in chronic kidney disease, defects in the cellular levels of reduced pyridine nucleotides and GSH metabolism are associated with poor capacity to prevent oxidative damages of blood cells and to restore the extracellular redox [ 41 , 45 , 46 , 47 , 48 ]; even more evident is the case of chronic respiratory syndromes that induce defects in the levels of lung GSH and in the redox buffering of protein Cys (reviewed in [ 7 , 34 , 35 , 36 , 49 ] and references therein). Worthy of note is the fact that such prototypical examples of chronic ailments, and others associated with oxidative stress, are included in the comorbidity that increases the risk of severe COVID-19 [ 6 , 50 ].…”
Section: Age-dependent Changes Of Lung Thiols and The Role Of Gsh In ...mentioning
confidence: 99%
“…These latter include the transcriptional and metabolic processes associated with adaptive homeostasis mechanisms discussed earlier in Section 2 , and these defects are exacerbated in case of premature aging and oxidative stress induced by chronic and degenerative ailments. For example, in chronic kidney disease, defects in the cellular levels of reduced pyridine nucleotides and GSH metabolism are associated with poor capacity to prevent oxidative damages of blood cells and to restore the extracellular redox [ 41 , 45 , 46 , 47 , 48 ]; even more evident is the case of chronic respiratory syndromes that induce defects in the levels of lung GSH and in the redox buffering of protein Cys (reviewed in [ 7 , 34 , 35 , 36 , 49 ] and references therein). Worthy of note is the fact that such prototypical examples of chronic ailments, and others associated with oxidative stress, are included in the comorbidity that increases the risk of severe COVID-19 [ 6 , 50 ].…”
Section: Age-dependent Changes Of Lung Thiols and The Role Of Gsh In ...mentioning
confidence: 99%
“…The nonenzymatic antioxidants include vitamins A, C, and E, bilirubin, and glutathione, while the enzymatic ones comprise glutathione peroxidase (GPX), superoxide dismutase (SOD), and catalase (CAT); taking into account that the enzyme defense system is the first rapid line of defense against ROS [ 20 , 21 ]. Total Thiol sulfhydryl (TSH) is an effective antioxidants that can preserve the correct structure of proteins, and can protect cells and tissues from damage induced by oxidative stress [ 22 ]. Free radicals can damage all macromolecules such as carbohydrates, proteins, lipids, and nucleic acids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress accompanies CKD, and the presence of ROS in the plasma of hemodialyzed patients has been demonstrated experimentally [15]. In patients with CKD, a significant decrease in the level of the thiol groups in proteins has also been shown [16,17]. The studies by Pieniazek and Gwozdzinski also showed conformational changes in hemolysate proteins in patients with CKD [16].…”
Section: Discussionmentioning
confidence: 96%